One-Pot Synthesis and Antioxidant Activity of 4-Phenoxyquinoline Derivative from Clove Leaf Oil - Lubis, Siti Masitah (Materials Science Forum, 2022)
Synthesis and antioxidant assay of 4-phenoxyquinoline derivative namely, (E)-7-chloro-4-(2-methoxy-4-(prop-1-en-1-yl)phenoxy)quinoline, from clove leaf oil have been conducted. This compound can be prepared from eugenol (isolated from clove leaf oil) in either two-step or one-pot synthesis. In two-step synthesis, eugenol was subjected to base-catalyzed-isomerization to give isoeugenol, which in turn underwent aromatic nucleophilic aromatic nucleophilic substitution with 4,7-dichloroquinoline to generate (E)-7-chloro-4-(2-methoxy-4-(prop-1-en-1-yl)phenoxy)quinoline in 57% total yields. By combining these two reactions, the 4-phenoxyquinoline derivative can be furnished in one-pot fashion in 63%. The results showed that the synthesized 4-phenoxyquinoline derivative, however, did not show strong antioxidant activity.